Comparison the Effectiveness of Silica Sand and Resin Filter Media on Reducing Phosphate Levels of Wastewater of PKU Muhammadiyah Hospital Surakarta - Asharani, Regita; Sugiharto, Agung; Khuzaimah, Siti; Estiyantara, Nurhadi (Jurnal Teknologi Bahan Alam, 2024)
Liquid waste containing phosphates has an effect on human health. Phosphate levels based on the results of preliminary tests carried out at the PKU Muhammadiyah Hospital in Surakarta were 5.7 mg/L; these results exceeded wastewater quality standards. There are many ways to reduce phosphate levels to comply with wastewater quality standards, including adding PAC coagulants, alum, and others. However, this is less effective when applied to hospital wastewater, so the researchers used the filtration method to reduce phosphate levels. The filtration method is a filtering process that separates particles or sediment so that they are not carried away with the treated water ready for discharge. The filter media used include zeolite, activated carbon, resin, silica sand, and many more. In this research, only two filter media were used, comparing the effectiveness of silica sand and resin filter media. Processing used variations in column height of 60 cm, 80 cm, and 100 cm, employing slow filter filtration experimental methods and laboratory tests to reduce phosphate levels in wastewater from PKU Muhammadiyah Hospital Surakarta.